Social Entrepreneurship Conceptual Approaches - Alcides Almeida Monteiro; José Carlos Sánchez-García; Brizeida Raquel Hernández-Sánchez; Giuseppina Maria Cardella (Encyclopedia, 2022)
Social entrepreneurship defines organizations or initiatives that, by producing and/or transacting goods or services, seek new solutions to persistent social problems, thus generating high social value. In other words, that deliberately subject their economic strategy to social priorities and place the social mission at the center of their concerns. Such social priorities include poverty, unemployment, education, health, local development, or the environment. Outside this common base, the aggregation of other characteristics or delimitations has given rise to conceptual fuzziness, namely, as to the organizational forms to be adopted (restricted to non-profit organizations or open to for-profit businesses with clear social purposes) and the weight of the social dimension in SE. Another manifestation of conceptual malleability emerges from the coexistence of different schools of thought. On the opposite side, one notes the narrowing of the concept, which mainly derives from a Westernized vision and still pays little attention to the contributions from developing countries. In addition to analyzing these topics, the current entry points out some recommendations regarding the deepening of scientific research in this field.